2018
DOI: 10.3389/fncel.2018.00175
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Intrinsic Properties Shape Functional Phenotype of Low-Frequency Neurons in the Auditory Brainstem

Abstract: In the auditory system, tonotopy is the spatial arrangement of where sounds of different frequencies are processed. Defined by the organization of neurons and their inputs, tonotopy emphasizes distinctions in neuronal structure and function across topographic gradients and is a common feature shared among vertebrates. In this study we characterized action potential firing patterns and ion channel properties from neurons located in the extremely low-frequency region of the chicken nucleus magnocellularis (NM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 69 publications
0
25
0
Order By: Relevance
“…Resurgent sodium current promotes the recovery of Na V channels. (A and E) Representative current traces recorded from mid- to high-frequency (A) NM and (E) NMc neurons, in response to two voltage-clamp protocols (for details, please refer Hong et al 43,50 ). In short, a conditioning step was applied to neurons followed by recovery period at rest for the varying amounts of time.…”
Section: Functional Specialization In Nmmentioning
confidence: 99%
See 1 more Smart Citation
“…Resurgent sodium current promotes the recovery of Na V channels. (A and E) Representative current traces recorded from mid- to high-frequency (A) NM and (E) NMc neurons, in response to two voltage-clamp protocols (for details, please refer Hong et al 43,50 ). In short, a conditioning step was applied to neurons followed by recovery period at rest for the varying amounts of time.…”
Section: Functional Specialization In Nmmentioning
confidence: 99%
“…Recent findings demonstrated that NMc neurons located in the low-frequency region present with distinct intrinsic properties and appear to function differently from mid- to high-frequency NM neurons. 19,43 The firing activity and excitability of NMc neurons are notably different from the rest of NM neurons. In response to sustained current injection, NMc neurons are able to fire repetitively, while mid- to high-frequency NM neurons fire a single-onset AP (Figure 3D and F).…”
Section: Tonotopic Heterogeneity Of Kv and Nav Channels In Nmmentioning
confidence: 99%
“…The latter would argue for gradients of dendritic properties along the tonotopic axis of the ventral cochlear nucleus. For the avian homologue of the VCN, the nucleus magnocellularis, it was established that gradients of biophysical parameters (Fukui and Ohmori, 2004;Oline et al, 2016;Hong et al, 2018), especially voltage activated potassium conductances, optimize temporal coding for a given range of input frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…We observed no relationship between cell type and location within NA, although tonotopic and anatomical differences were beyond the scope of this study, so they cannot be ruled out. Tonotopic differences in intrinsic, synaptic, morphologi-cal, and neurochemical markers have been observed in NM (Akter et al 2018;Fukui and Ohmori 2004;Hong et al 2018aHong et al , 2018bKöppl 1994;Kuba and Ohmori 2009;Oline et al 2016;Oline and Burger 2014;Wang et al 2017) and NA (Ahn and MacLeod 2016;Bloom et al 2014;Carr and Boudreau 1991;Levin et al 1997;Soares and Carr 2001), so it is possible that tonotopic gradients exist.…”
Section: Discussionmentioning
confidence: 99%
“…Similar parallel processing exists in birds, where the cochlear nucleus angularis (NA) extracts intensity information from the acoustic stimulus and nucleus magnocellularis (NM) extracts timing information (Carr and Konishi 1990;Fukui et al 2006;Joseph and Hyson 1993;Köppl and Carr 2003;Overholt et al 1992;Parks and Rubel 1975;Sato et al 2010;Sullivan and Konishi 1984;Warchol and Dallos 1990). NM contains intrinsic and synaptic specializations for encoding temporal information from the auditory nerve (Ahn and Ma-cLeod 2016;Fukui et al 2006Fukui et al , 2010Fukui and Ohmori 2004;Hackett et al 1982;Hong et al 2018aHong et al , 2018bHoward and Rubel 2010;Jackson and Parks 1982;Köppl 1994Köppl , 1997Levin et al 1997;Oline et al 2016;Parks 1981Parks , 2000Parks and Rubel 1978;Raman et al 1994;Rathouz and Trussell 1998;Reyes et al 1994;Stincic and Hyson 2011;Trussell 1994a, 1994b). Across the tonotopic axis, both intrinsic and synaptic features are tuned to optimize temporal information processing of different acoustic frequencies (Oline et al 2016; Oline and Burger 2014), and the interplay between inhibition and low-threshold K ϩ current (I LT ) varies along the tonotopic axis of nucleus laminaris, the downstream target of NM, where interaural time differences are compared for sound localization (Hamlet et al 2014).…”
Section: Introductionmentioning
confidence: 98%